Optimizing clinical outcomes in polypharmacy through poly-de-prescribing: a longitudinal study - Garfinkel, Doron; Levy, Yuval (Frontiers in Medicine, 2024)
Objectives To evaluate polypharmacy in older people to determine whether the number of medications de-prescribed correlates with the extent of improvement in quality of life (QoL) and clinical outcomes. Design A prospective longitudinal cohort study of polypharmacy in people living in a community in Israel. Setting Participants aged 65 years or older who took at least six prescription drugs followed up for at least 3 years (range 3–10 years) after poly-de-prescription (PDP) recommendations. Interventions PDP recommended at first home visit using the Garfinkel algorithm. Annual follow-up and end-of-study questionnaires used to assess clinical outcomes, QoL, and satisfaction from de-prescribing. All medications taken, complications, hospitalizations, and mortality recorded. In total, 307 participants met the inclusion criteria; 25 incomplete end-of-study questionnaires meant 282 participants for subjective analysis. Participants divided into two subgroups: (i) those who discontinued more than 50% of the drugs (PDP group) or (ii) those who discontinued less than 50% of the drugs (non-responders, NR). Main outcome measures Objective: 3-year survival rate and hospitalizations. Subjective: general satisfaction from de-prescribing; change in functional, mental, and cognitive status; improved sleep quality, appetite, and continence; and decreased pain. Results Mean age: 83 years (range 65–99 years). Mean number of drugs at baseline visit: 9.8 (range 6–20); 6.7 ± 2.0 de-prescribed in the PDP group (n = 146) and 2.2 ± 2.1 in the NR group (n = 161) (p < 0.001). No statistical difference between the groups in the 3-year survival rate and hospitalizations, but a significant improvement in functional and cognitive status and, in general, satisfaction from the intervention in the PDP group compared to the NR group. Improvement usually evident within the first 3 months and persists for several years. Conclusion Poly-de-prescribing in the older population has beneficial effects on several clinical outcomes with no detrimental effect on the rate of hospitalization and survival. The extent of improvement correlates with the extent of de-prescribing. Applying the Garfinkel algorithm globally may improve QoL in millions of patients, a clinical and economic win–win situation.